Властивості нанокристалічних порошків у системі ZrO₂−Y₂O₃−CeO₂−Al₂O₃ у ході термічної обробки при 400–1300 °С - Дуднік, О.В.; Шевченко, О.В.; Рубан, О.К.; Редько, В.П.; Лопато, Л.М. (Видавничий дім "Академперіодика" НАН України, 2008)
Special features of the processes running in the nanocrystalline powders 90 wt. % ZrO₂ (8CeO₂, 2Y₂O₃) 10 wt. % Al2O3 and 10 wt. % ZrO₂ (8CeO₂, 2Y₂O₃) 90 wt. % Al₂O₃ on continuous heat treatment at 400–1300 °С are determined. It is found that the ordering of powders related to the transition from a disordered chaotic condition through a build-up of fluctuations to the formation of new intermediate phases occurs. The obtained results are used in the design of bioimplants and multilayer cutting tools for medicine.